Screening key genes and microRNAs in sepsis by RNA-sequencing. Issue 1 (January 2020) - Qin, Yanjun; Guo, Xuan; Yu, Yueqing; Dong, Shimin; Yan, Yan; Bian, Xiaohua; Zhao, Caiyan
Abstract : Background: Sepsis is a life-threatening organ dysfunction, initiated by a dysregulated host response to infection. This study aimed to determine key genes and microRNAs (miRNAs) correlated with sepsis. Methods: Three patients with sepsis and three healthy individuals treated as controls were recruited in the current study. To identify differentially expressed mRNAs (DEmRNAs) and differentially expressed miRNAs (DEmiRNAs) between patients with sepsis and controls, RNA-sequencing and bioinformatics analysis were conducted. DEmiRNA-target DEmRNAs analysis and functional annotation of DEmiRNA-target DEmRNAs were performed. Dataset GSE46955, used to validate the expression of selected DEmRNAs, was downloaded from the Gene Expression Omnibus database. Results: Compared with septic patients, a total of 1199 DEmRNAs and 23 DEmiRNAs were identified. Based on DEmiRNA-target DEmRNAs analysis, hsa-miR-106b-5p (degree = 155), hsa-miR-128-3p (degree = 128), and hsa-miR-144-3p (degree = 79) were the top 3 DEmiRNAs that covered most DEmRNAs. The T cell receptor signaling pathway, pathways in cancer, FoxO signaling pathway, and influenza A were the significantly enriched Kyoto Encyclopedia of Genes and Genomes pathways of DEmiRNA-target DEmRNAs in sepsis. Conclusion: We identified key genes and miRNAs related to sepsis. Our findings will provide new insights into understanding sepsis pathogenesis.